Keterkaitan Motivasi Kuasa, Motivasi Afiliasi Dan Motivasi Prestasi Terhadap Tingkat Keberhasilan Petani Hortikultura Dataran Tinggi - Prasetyo Nugroho, Anung; Setyowati Suroto, Karunia (Hasanuddin University, 2024)
Caused by various external and internal factors that affect the success of horticultural farmers. This research was conducted with the aim of knowing the relationship between power motivation, affiliation motivation and achievement motivation to the success rate of highland horticultural farmers in Magetan Regency. The two hypotheses tested were (1) power motivation, affiliation motivation and achievement motivation simultaneously affect the success of upland horticultural farmers in Magetan District, Magetan Regency, and (2) achievement motivation is the most influential motivation on the success of upland horticultural farmers in Magetan District, Magetan Regency. Fifty respondents were randomly selected from 252 horticultural farmers in Magetan District. Data validity was tested with the Pearson Product Moment approach, and data reliability was tested with the Reliability Analysis Scale (alpha) approach. Hypothesis 1 is tested through the F-test of regression coefficients at p < 0.05. Hypothesis 2 was tested through t-test of partial regression coefficients at p < 0.05. The results showed that power motivation, affiliation motivation and achievement motivation simultaneously affect the success of highland horticultural farmers in Magetan District, Magetan Regency. Affiliated motivation is the most important motivation that affects the success of upland horticultural farmers in Magetan District, Magetan Regency. Power motivation, affiliation motivation and motivation contributed 70.3% to the variation in the success of horticultural farmers. Affiliation motivation and power motivation contributed 69.8%, and achievement motivation contributed only 0.5% to the variation in the success of horticultural farmers.